Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Usaha Pada Umkm Rendang Di Kota Payakumbuh - Mawaddah , Fauza; Ibnusina, Fedri; Alfikri, Alfikri (Green Engineering Society, 2023)
The purpose of this study is to analyze the influence of capital, ability, business location, marketing strategy and partnership system. The data formulation in this study uses quantitative descriptive methods. The results of this study indicate that the factors of ability, business location, marketing strategy and partnership system influence the success of the business at Rendang UMKM in Payakumbuh City and the capital variable does not significantly influence the success of the business. Variable capital, ability, business location, marketing strategy and partnership system simultaneously (together) affect the success of the business as a dependent variable. This is evidenced by the results of the f test, obtained f arithmetic> f table that is 19,371> 2,621 or a probability of 0,000 <0.05. Then it can be concluded that H0 is rejected and H1 is accepted. statistical calculation of the coefficient of determination with the adjusted R Square value of 0.763 or 76.3%. This shows that the percentage contribution of the influence of independent variables namely capital, ability, business location, marketing strategy and partnership system to business success is 76.3% or the variation of the independent variables used is able to explain at 76.3% the dependent variation. While the remaining 23.7% is influenced by other variables not included in this research model.